Efficacy of Dietary Management on Albuminuria and Renal Markers in Cases of Diabetic Nephropathy- A Randomised Control Study - Jyoti Prakash (Advancement and New Understanding in Medical Science Vol. 9, 2024)
Introduction: Diabetes mellitus (DM) is a non-communicable disease that affects various organs of our body by micro as well as macro vascular dysfunction. Diabetic kidney disease (DKD) is the most common cause of end-stage kidney disease (ESKD) in developed countries [1]. It is thought to be a micro vascular issue that impacts both type 1 (T1DM) and type 2 (T2DM) diabetic patients. Chronic albuminuria and a progressive decrease in glomerular filtration rate are the hallmarks of the condition. Strong evidence suggests that early treatment of the illness can halt or delay its progression. The estimated GFR (eGFR) and urine albuminuria are two trustworthy diagnostics for diagnosis and monitoring. Adequate blood pressure management and ideal glycemia are necessary to halt the advancement of diabetic kidney disease (DKD) [2]. The study aims to provide valuable insights into the effectiveness of dietary management in ameliorating renal dysfunction in diabetic nephropathy, potentially influencing clinical practice and improving patient outcomes. Materials and Methods: 200 patients were randomly selected and grouped into A, B, C, and D containing 50 patients in each group. Group A and B had hypertensive patients with low and high protein diet given respectively for 24 weeks. Group C and D had normotensive patients with low and high protein diet given respectively for 24 weeks. 24 hours urinary albumin (mg/day) excretion rate, Blood urea, Serum creatinine, Urine creatinine, Creatinine clearance were estimated initially and at 24 weeks. Results: The mean albuminuria in Group A dropped significantly from 1702±360.41 (baseline) to 1169±276.86 (24th week), with a p value of less than 0.0001. With a p-value of less than 0.0001, the mean albuminuria in Group B increased significantly from 1706±251.44 (baseline) to 2023±301.50 (24th week). The mean albuminuria in Group C dropped significantly from 1279.80±178.62 (baseline) to 826.60±186.39 (24th week), with a p value <0.0001. With a p-value of less than 0.0001, the mean albuminuria in Group D increased significantly from 1288.6±101.01 (baseline) to 1484±151.6 (24th week). Conclusion: Patients with diabetic nephropathy benefit generally from dietary protein restriction. The impact is most likely the result of enhanced glomerular permeability and selectivity and is unaffected by variations in blood pressure or blood glucose.